New Green Modalities of Flow Injection Technology for Assaying Anti-Allergic Drugs in Pharmaceutics and Biological Samples - L. Hamed, Shahad; B. Qassim , Bushra (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
A new approach and the developed FIA technique with many advantages (economic, fast, simple, accurate, and high throughput) are used to determine the decongestant drugs (Phenylephrine.HCl, Oxymetazoline.HCl) in biological samples, pharmaceutical formulations, and pure samples via continuous flow injection technique by oxidative coupling reaction, where the method depends on the interaction of the decongestant drug with organic reagents to produce colored compounds, where Phenylephrine reacts with 4-AAP at λmax503 nm to produce a red compound, and the Beer’s law range of 10-600 μg.mL-1 . As for Oxymetazoline, it reacts with DNPH at λmax 631nm to produce a green compound with a linear dynamic range of 5-400 μg/mL. The limits of detection were 9.24 and 4.67 μg.mL-1, respectively. The veracity of recovery (%) was 100.24, 100.68, RSD% were 3.44, 2.51 and sampling was 60,77 sample.h-1 for PHE and OXY successively. Distilled water was used as a carrier to transport chemicals within the minute ports of the new system. Statistical data treatment using analysis of variance one-way ANOVA was used for the determination of drugs in dosage forms, and the results obtained were compared with the official method (AOAC) and British pharmacopeia.